Murder the truth: fear, the First Amendment, and a secret campaign to protect the powerful - Enrich, David (Mariner Books, 2025)
"It seemed like a throwaway line in a forgettable opinion: In 2019, Supreme Court Justice Clarence Thomas raised the prospect of challenging the legendary Warren Court decision New York Times v. Sullivan. Though hardly a household name, Sullivan is one of the most consequential free speech decisions, ever. Fundamental to the creation of the modern media as we know it, it has enabled journalists and writers all over the country-from top national publications to revered local newspapers to independent bloggers-to pursue the truth aggressively and hold the wealthy, powerful, and corrupt to account. Thomas's words were a warning-the public awakening of an idea that had been fomenting on the conservative fringe for years. With that opinion, Thomas took mainstream the ongoing, secret efforts of right-wing politicians, activist lawyers, and moneyed elites who had been seeking to overturn Sullivan in order to muzzle the media and their critics. From the Florida statehouse to small town New Hampshire to Donald Trump himself, this movement consists of powerful individuals who believe they should be above scrutiny-and are using threats, subterfuge, and legal warfare to get their way. In this masterwork of investigative reporting, David Enrich, New York Times Business Investigations Editor, traces the roots and reach of this new threat to our modern democracy. Laying bare the stakes of losing our most sacrosanct rights, Murder the Truth is a story about power-the way it's used by those who have it, and the lengths they will go to avoid it being questioned"-- Provided by publisher